Facebook Intrusion as a Mediator Between Positive Capital and General Distress: A Cross-Cultural Study - Przepiorka, A. (2021)
Social networking sites (SNSs) play an important role in many aspects of life nowadays, and it seems to be crucial to explore their impact on human well-being and functioning. The main aim of the study was to examine the mediating role of Facebook intrusion between positive capital and general distress. Positive capital was considered as comprising self-esteem, ego-resiliency, and self-control, while general distress was seen as having three dimensions: depression, anxiety, and stress.